Competency-based education – the reform of postgraduate medical training in Switzerland - Schwitz, Fabienne; Brodmann Maeder, Monika; Hennel, Eva K. (GMS Journal for Medical Education)
Objective: Medical training in Switzerland is currently undergoing change. The postgraduate education curricula of all medical specialties are being converted to competency-based medical education (CBME). Entrustable Professional Activities (EPA) are used to assess competencies. EPAs describe specific professional tasks that are assigned to postgraduate trainees once they have achieved sufficient competencies.Methodology and results: The article describes how the didactic building blocks are joined to create competency-based teaching and how the implementation takes place.The project is described using the Kern cycle. The first two steps, problem identification and targeted needs assessment, are presented in the project description section, the other four steps in the results. Concrete details are given using examples from the cardiology curriculum.Conclusion: The conversion of medical training in Switzerland to competency-based teaching is an important step that is urgently needed but complex. The long-term plan of the Swiss Institute for Postgraduate and Continuing Medical Education (SIWF) consists not only of structural steps but also cultural change. The first two years of the conversion were successful. In collaboration with the specialist societies, postgraduate curricula are being converted to EPA-based learning objectives, the didactic training for postgraduate teaching staff adapted accordingly and feedback from learners is continuously gathered. The implementation process has begun. Additional data will be collected as the project proceeds. Using experience already gained internationally and by specialist societies which have already taken this step as benchmarks is critical for other specialties and training centres that are still to follow.